BIODIVERSITY AND RELATIONSHIP ROSE APPLE (Syzygium aqueum Burm.f. Alston) MORPHOLOGICAL APPROACH THROUGH NATURE IN PLANTATION Bhakti, PASURUAN - Hamidah, Hamidah; Junairiah, Junairiah; Mardiastuti, Devi (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v6i1.1204, 2015)
The  aims  of  this  study  were  to  examine  whether  there  is  diversity  of  morphological  from  variety of  rose  apple  (Syzygium  aqueum  Burm.f.Alston),  analize  their  relationship  and  find  out  the characteristics  that  effects  the  classification  of  these  rose  apple.  This  study  itself  is  using  the descriptive  approach.  Sampling  is  taken  at  some  sites  Plantation  Bhakti   Alam  Ngembal  Village Tutur  Subdistrict  Pasuruan  Regency,  East  Java.  The  result  of  the  research  finds  four  varieties Camplong,  Citra,  Black  Diamond,  and  Pink  Rose  Apple.  Parts  of  the  plants  to be studied are 55 characters,  including  plant  high,  leaf  side,  corolla  high,  and  corolla  width.  Morphological  of variety  of  rose  apple  were  analyzed  by  SPSS  programme.  This  programme  used  simple  matching coefficient  that  use  to  form  dendrogram.  The  dendrogram  resulted  two  main  groups  of  rose  apple group  A  and  group  B.  Group  A  consisted  of  variety  of  Pink  Rose  Apple  with  75,1%  similarity value.  In  the  PCA  (Principal  Component  Analysis)  analysis  of  characters  that  effect  the  grouping of  variety  of  rose  apple  leaves  thickly,  high  plants,  leaf  type,  leaf  edge,  leaf  point,  leaf  wide,  leaf length,  stalk  leaf  length,  leaf  distance  accompany ,  diatance  bone  leaves,  calyx  shape,  high corolla,  corolla  width,  high  fruit,  fruit  diameter,  fruit  skin  surface,  fruit  flavor,  seed  color, number  of seed, form  of seed, diameter  of seed, and long  seed.